Role of gender and age in features of Wilson’s disease - Cai, Lin; Huang, Xiaotao; Ye, Yan; Yang, Dailan; Xie, Linshen; Fu, Daigang; Peng, Lijun; Zhou, Dingzi; Liao, Juan (Frontiers in Neurology, 2023)
Background Wilson’s disease (WD) is a recessive genetic disorder characterized by copper metabolism dysfunction. It is difficult to obtain an accurate diagnosis due to its variable clinical presentation. This study aimed to describe the clinical characteristics and diagnostic particularities in a series of Chinese WD patients. Methods The medical records of 371 patients with WD retrieved from January 2005 to December 2020 were retrospectively reviewed. Results The incidence of WD has a male predominance in the adult population. However, the difference in sex distribution is not significant in the pediatric population. Females have an earlier symptom onset than males. The most common initial symptoms were neuropsychiatric manifestations both in the pediatric population (49.7%) and adult population (69.8%), and there was a male predominance (61.8%). Eighty-two percent of patients presented with more than two neurologic symptoms. Fifty-two (14%) patients presented with psychiatric symptoms. The most common WD phenotype was the neuropsychiatric form (48%). The age of onset occurred earlier in patients with the hepatic phenotype than in those with the neuropsychiatric phenotype. Moreover, there was a significant difference in sex distribution regarding phenotype. Females presented with a hepatic phenotype more often than males, and the neuropsychiatric phenotype occurred more frequently in males with an older onset age. Further study showed that the age at onset was a deciding factor for predicting the neuropsychiatric phenotype among the hepatic phenotype. However, sex did not correlate with the phenotype. Conclusion Males seem to have a higher disease susceptibility, with symptom onset later than females. Males frequently present with a neuropsychiatric phenotype, while females present with a hepatic phenotype. Age at onset was a deciding factor for predicting the WD phenotype. Further studies focusing on the effect of estrogens on the pathology of WD are suggested.